A study of the attitudes of student teachers toward use of computer - Aijaz Ahmed Gujjar; Muhammad Naeemullah; Rabia Tabassum (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The importance of information and communication Technology (ICT) in education, and particularly in teacher education, is being widely acknowledged. An important prerequisite of ICT is knowledge and attitude towards the use of computers. This descriptive study was aimed at finding out the attitude of student teachers toward the use of computer. Forty item questionnaire was constructed covering five dimensions i.e (fear of using computer, problem solving by computer, computer knowledge, using computer and learning computer). Two hundred student teachers from Federal College of Education were considered the sample of the study. Data were collected and analyzed by applying independent sample t-test and ANOVA. The study reveals that male and female students have the same attitude on all dimensions of the scale, those students who have computer at home are significantly better than their counterparts on fear of using computer and computer knowledge, there is a significant difference among students on computer knowledge regarding mothers' qualification and there is no significant difference on any dimension of the scale regarding fathers' qualification. The study recommends that the student teachers should be exposed more and more to computers so as to overcome the fear of using computers and get optimum benefit by using computer.
Keywords: 330; use of computer; attitude of student teacher; mothers' qualification; fathers' qualification